2018
DOI: 10.3389/fpsyg.2018.02649
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence Buffers the Effects of Negative Emotions on Job Burnout in Nursing

Abstract: The study was designed to examine whether trait emotional intelligence would moderate the impact of negative emotions at work on job burnout. A total of 188 female nurses participated in this study and completed measures of trait affectivity, emotional intelligence, anger and sadness at work, and burnout. The results revealed significant and positive relationships between both types of negative emotions and burnout above and beyond demographics and the nurses’ trait affectivity. Importantly, the study demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 82 publications
5
78
0
7
Order By: Relevance
“…Therefore, higher scores in emotional intelligence indicate that those nursing professionals are able to minimize the intensity and presence of negative emotions, which consequently, have a positive repercussion on management of stressful situations and protect against burnout. Along this line, the role of emotional intelligence as a moderator in the relationship between negative emotions and burnout is proposed [26]. Meta-analyses have also previously corroborated the relationships between emotional intelligence based on capacity and job performance [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, higher scores in emotional intelligence indicate that those nursing professionals are able to minimize the intensity and presence of negative emotions, which consequently, have a positive repercussion on management of stressful situations and protect against burnout. Along this line, the role of emotional intelligence as a moderator in the relationship between negative emotions and burnout is proposed [26]. Meta-analyses have also previously corroborated the relationships between emotional intelligence based on capacity and job performance [27].…”
Section: Introductionmentioning
confidence: 99%
“…Job burnout is defined as "a psychological syndrome in response to chronic interpersonal stressors on the job" (Maslach et al 2001, p. 399). Feelings of burnout within the context of one's job may arise due to a variety of reasons including increasing perceptions of an overall lack of support/access to external resources (Hakanen et al 2006;Huebner 1992;Schilling et al 2018;Williams and Gersch 2004), increasing job demands (Evers et al 2004;Hakanen et al 2006;Ilies et al 2015;Richards et al 2016;Schilling et al 2018;Williams and Gersch 2004), strained relationships with coworkers (Grayson and Alvarez 2008;Schilling et al 2018;Zhao et al 2018), reduced access to internal resources/ perceptions of an individual's ability to do one's job and to cope with difficult situations (Alessandri et al 2018;Butler and Constantine 2005;Skaalvik and Skaalvik 2007), and increased feelings of negativity (Bianchi and Schonfeld 2016;Szczygiel and Mikolajczak 2018).…”
Section: Defining Job Burnoutmentioning
confidence: 99%
“…Related to increasing motivation/resilience in workers as a method of addressing feelings of job burnout, many have argued that increasing feelings of self-efficacy should also be a target of such efforts. Feelings of self-efficacy in relation to the ability to successfully navigate the work team climate (Loeb et al 2016), the ability to effectively cope with work stressors (Evers et al 2004), and the ability to deal with negative emotions at work (Alessandri et al 2018;Szczygiel and Mikolajczak 2018;Zhao et al 2018) have all been found to lessen the burden of feelings of job burnout. In recognizing the importance of these personal characteristics in preventing and responding to feelings of burnout, some researchers have proposed that methods aimed at increasing feelings of resilience and self-efficacy are perhaps the most effective means of dealing with the issue of job burnout.…”
Section: Strategies For Addressing Burnoutmentioning
confidence: 99%
“…The central theme in this study was research articles containing "emotional intelligence" in the title and abstract. The oldest publication dates to 1966 [17] and the more recent ones are from 2018 [18]. The query string used for the search was: (TITLE-ABS ("emotional intelligence")) AND (LIMIT-TO (DOCTYPE, "ar")) AND (LIMIT-TO (SRCTYPE , "j")) AND (EXCLUDE (PUBYEAR , 2020) OR EXCLUDE (PUBYEAR, 2019)).…”
Section: A Data Source and Search Strategymentioning
confidence: 99%